Model Bisnis Start-Up Digital Di Era Ekonomi Digital - Putri Effendi, Meilany; Nasution, Nisa Ul Mahfuzha; Nabila Balqis (Perkumpulan Konsultan Manajemen Pendidikan Indonesia (PKMPI), 2025)
The development of information and communication technology has driven a major transformation in the global economic landscape, giving rise to the digital economy era, which demands adaptation and innovation across various sectors, including start-up businesses. This study aims to examine digital start-up business models emerging in the digital economy era, focusing on key elements such as value proposition, revenue structure, customer acquisition strategies, and the utilization of digital technologies. A qualitative approach is employed through literature reviews and case analyses of digital start-ups in various sectors, such as e-commerce, edutech, fintech, and healthtech. The findings indicate that adaptive, platform-based, and customer-centric business models are crucial for start-up success in this era. Furthermore, the ability to build digital ecosystems, establish strategic partnerships, and integrate data as a core business asset are determining factors in creating sustainable competitive advantages. This study contributes to the understanding of digital business dynamics and offers practical insights for entrepreneurs, investors, and policymakers in supporting the growth of start-ups in the digital economy